An immune cell activation signature reflected hepatocellular carcinoma heterogeneity and predicted clinical outcomes - Wang, Xiaofeng; Liu, Dongli; Wang, Shuai; He, Rui (Frontiers in Immunology, 2025)
BackgroundThe prognosis of hepatocellular carcinoma (HCC) remains challenging, and immune activation plays a critical role in cancer treatment. Identifying reliable immune activation-related prognostic markers is critical for predicting HCC patient outcomes.MethodA six-gene signature was developed. The prognostic value was assessed by correlating the signature and survival. The robustness of the signature was validated in three independent Gene Expression Omnibus (GEO) datasets. Associations with clinical, genomic, and transcriptomic features were also evaluated. Additionally, single-cell sequencing data were analyzed to explore cell–cell interaction heterogeneity reflected by the signature. The biological role of candidate gene RORC was investigated, including chemotherapy resistance and detailed regulatory mechanism in affecting progression. The clinical potential role of RORC and its downstream gene was also evaluated by immunohistochemical (IHC) microarray.ResultsThe six-gene signature stratified patients into high-risk and low-risk groups, with high-risk samples exhibiting significantly shorter overall survival (median: 23.8 months, 95% CI: 20.6–41.8) than low-risk samples (median: 83.2 months, 95% CI: 69.6–NA, p < 0.001). Validation in independent GEO datasets confirmed the robustness of the signature. The signature was significantly associated with the pathological stage and negatively correlated with PD-L1 expression, outperforming clinical indicators in predicting 3-year survival. The signature was significantly associated with TP53 mutations, genomic stability, and canonical cancer-related pathways. Single-cell sequencing data indicated that the signature revealed cell–cell interaction heterogeneity in HCC. Candidate gene RORC promotes proliferation and migration by regulating CDC6 gene expression as a transcription factor. Furthermore, RORC is also associated with multiple drug resistance, especially docetaxel and paclitaxel. IHC revealed that RORC and candidate gene CDC6 were valuable predictive biomarkers for prognosis.ConclusionThe six-gene signature provides valuable insights into the biological status of HCC patients and is a robust tool for clinical application.